Usuários de serviços de saúde mental e risco para DST: vulnerabilidade e confiabilidade - Helian Nunes de Oliveira (2006)
Mental ill patients (MIP) are known to be vulnerable to HIV and other sexually transmited diseases (STD), e.g. syphilis, hepatitis B and C. However, well designed studies and reliable instruments that describe risk behavior and factors associated with HIV and STD in this population are still necessary. Thus, a multicenter study, sponsored by the AIDS National Program (PN-DST/AIDS Brasil) and the Mental Health Coordination, Ministry of Health, has been developed by the Research Group in Epidemiology and Health Care Evaluation, FederalUniversity of Minas Gerais (GPEAS/FM/UFMG), (PESSOAS PROJECT). A pilot study was conducted in order to assess feasibility, reliability and validity issues, object of this dissertation. The pilot study was conducted in one public psychiatric hospital and in one public mental health outpatient clinic. Participants were randomly selected (n=90) and invitedfor an interview and serology testing: HIV, hepatitis B and C and syphilis. In addition to a reliability analysis, vulnerability profiles were provided using Grade of Membership approach (GoM). Reliability assessment indicated kappa statistics and intraclass correlation coefficient(ICC) ranging from reasonable to excellent, both for intra and inter-raters. Final GoM analysis included 15 variables and generated three vulnerability profiles. The first profile mainly reflected a high proportion of adult women, living with a companion, who denied any pastSTD history, and reported lack of condom use in the last 6 months or in the last sexual intercourse. They also reported some kind of sexual violence, denied any risk of acquiring AIDS, had up to 10 sexual partners in their lifetime, and denied any illicit psychoactivesubstance use or exchange of sex for money or drugs. The second profile was predominantly composed of men, 35-43 years old, in conjugal union, with a history of homelessness and STD, alcohol use, irregular condom use in last the 6 months, sexual partners refusal to use condom. In addition, they reported not using condom in the last sexual intercourse, indicated some risk of acquiring AIDS, had more than 10 sexual partners in the life, used illicit drugs in their lifetime and psychoactive substance during sex and exchanged sex for money or drugs. The third profile consisted of men, 18-34 years old, single or in union in the past. In addition, they denied history of homelessness, STD or alcohol use, and reported always using condom or did not have sex in the last 6 months. They also denied refusal of the partner to usecondom, used condom in the last sexual relation, indicated no risk of acquiring AIDS, had up to 10 sexual partners in their life, used illicit drugs in their lifetime and denied psychoactive substance use during sexual relations. The use of GoM model generated vulnerability profiles among mental ill patients compatible with the literature. This result, inaddition to the reasonable reliability assessment, indicates the suitability of the tested instrument.